A nitrogen budget for the Cape Metropolitan area : is nitrogen enrichment occurring in the soils of remnant patches of lowland fynbos? - Kathawaroo, Deshika (Department of Biological Sciences, 2017)
Anthropogenic activities create nitrogenous pollutants which threaten the existence of lowland fynbos, comprising 92 Red Data Book species and 14 Cape Flats endemics. A regional Nitrogen budget was constructed through the collation of existing data for the Cape Metropolitan Area. An NOx inventory has revealed that vehicles emit 66 % of the total NOx emissions into the atmosphere. The maximum potential N deposition is 184 kg N ha⁻¹ yr⁻¹ for the lowlands. Air quality in an industrial area, Goodwood, has revealed that a large proportion of the emissions remain in the air and have the potential to deposit 33 kg N ha⁻¹ yr⁻¹. Atmospheric N deposited on unimpacted coastal fynbos is 1.99 kg ha⁻¹ yr⁻¹. Thus remnant patches of lowland fynbos are threatened by replacement by grasslands as a result of atmospheric N inputs. Direct measurements of soil N pools are required, since signals of leaching in rivers may be premature as N accumulating in soil pools may not yet have reached saturation point. NH₃ emissions, wet and dry N deposition, and atmospheric transport models are required in order to construct a N budget for the CMA. Thereafter, appropriate preventative strategies can be devised in order to prevent the replacement of remnant patches of lowland fynbos.